Induksi Kalus dan Regenerasi Tanaman pada Kultur Antera Persilangan Padi Indica Varietas Lokal Bengkulu - Herawati, Reny; Rustikawati, Rustikawati; Inoriyah, Entang (Akta Agrosia, 2015)
Establishment of homozygous lines can be accelerated with anther culture technique that can produce pure lines in one generation. Formation of spontaneous double haploid plants in rice anther culture is very beneficial, because it does not need to be doubled haploid plants as material selection.This study aims to obtain a doubled haploid lines of upland rice is tolerant to drought and blast disease resistance. The main ingredient in this research is anther crosses of rice plants (F1), which consists of local varieties with selected lines of P1 (Sriwijaya x IR-148), P2 (Sriwijaya x IR-7858-1), P3 (Bugis x IR -148), and P4 (Bugis x IR-7858-1), callus induction media (N6), regeneration medium (MS). Anther culture of local varieties of rice indica/indica produced callus induction and plant regeneration are low, resulting in low efficiency of anther culture in providing green plants. The use of donor parents indica/j aponica which is responsive to anther culture into consideration for the material F1 crosses. Anther inoculation needs to be done in several stages so that the opportunity to obtain plantlets in sufficient quantities for material selection will be greater.